Rare Diagnosis of a Proliferating Pilar Tumor in a Facial Hairline Cryst - Imran, Farrah-Hani; Imami, Nabilah Hasna; Wen, Adzim Poh Yuen (Folia Medica Indonesiana, 2022)
Highlight: • Sebaceous cyst or epidermoid cyst is a benign capsulated tumour on the scalp region, face, neck, and trunk that subepidermal nodule filled with keratin. • Proliferating Pilar Tumours (PPT) are rare tumours was found in hair follicle. • Sebaceous cyst diagnose on facial hairline tumour turned out to be a rare Proliferating Pilar Tumour (PPT). Abstract: Sebaceous cyst, also known as an epidermoid cyst, is a subepidermal nodule filled with keratin and it is a benign capsulated tumor. It is often located on the scalp region, face, neck, and trunk; but can be found elsewhere such as the scrotum, genitalia, fingers, and buccal mucosa. Proliferating Pilar Tumors (PPT) are rare tumors. It is derived from the external root sheath of the hair follicle. These tumors are like irregular subcutaneous nodules and often appear on the scalp. This case report was about a 59 years old woman who came to the hospital following excision of a frontal lump elsewhere, with a sebaceous cyst as the initial diagnosis. From the histopathologic examination, grossly there was a whitish and greyish lump with a soft outer surface. Microscopically, there were malignancy signs with areas with keratinization. The tumor formed a solid pattern of enlarged cells with moderate to marked nuclear pleomorphism with vesicular nuclei, prominent nucleoli, and abundant pale eosinophilic to clear cytoplasm. There was also much free keratinous debris noted and numerous foci of calcification identified within the tumor. Mitotic figures with abnormal forms were frequently seen. The final diagnosis after the histopathological examination was Proliferating Pilar Tumour with focal malignancies. In conclusion, facial hairline tumor differentially diagnosed as a sebaceous cyst turned out to be a rare Proliferating Pilar Tumor (PPT). Following histopathological confirmation, the patient was referred for further management by a specialist team.